Effect of Heat Drawing Process on Mechanical Properties of Dry-Jet Wet Spun Fiber of Linear Low Density Polyethylene/Carbon Nanotube Composites - Jong Won Kim; Joon Seok Lee (International Journal of Polymer Science)
Polyethylene is one of the most commonly used polymer materials. Even though linear low density polyethylene (LLDPE) has better mechanical properties than other kinds of polyethylene, it is not used as a textile material because of its plastic behavior that is easy to break at the die during melt spinning. In this study, LLDPE fibers were successfully produced with a new approach using a dry-jet wet spinning and a heat drawing process. The fibers were filled with carbon nanotubes (CNTs) to improve the strength and reduce plastic deformation. The crystallinity, degree of orientation, mechanical properties (strength to yield, strength to break, elongation at break, and initial modulus), electrical conductivity, and thermal properties of LLDPE fibers were studied. The results show that the addition of CNTs improved the tensile strength and the degree of crystallinity. The heat drawing process resulted in a significant increase in the tensile strength and the orientation of the CNTs and polymer chains. In addition, this study demonstrates that the heat drawing process effectively decreases the plastic deformation of LLDPE.